Does Warfarin or Rivaroxaban at Low Anticoagulation Intensity Provide a Survival Benefit to Asian Patients With Atrial Fibrillation? - Lin, Dong; Chen, Yequn; Yong, Jian; Wu, Shiwan; Zhou, Yan; Li, Weiping; Tan, Xuerui; Liu, Ruisheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Low-dose rivaroxaban and low-intensity warfarin are widely used in Asia for patients with atrial fibrillation (AF). However, in Asians, it is unclear whether low-dose rivaroxaban and low-intensity warfarin can improve the prognosis of AF. In this study, we investigate the survival benefits of low-dose rivaroxaban and low-intensity warfarin in Asian patients with AF in clinical practice. Methods: This cohort study used medical records in a single tertiary hospital in China, between 2019 and 2020, to identify patients with AF who used rivaroxaban or warfarin, or had no anticoagulant therapy. Follow-ups were performed through telephone contact or medical record review. Cox proportional hazards models were used to compare the risk of mortality of patients in anticoagulant-untreated group versus warfarin-treated groups and rivaroxaban-treated groups. Results: A total of 1727 AF patients, discharged between 2019 and 2020, were enrolled in this cohort, of which 873 patients did not use any anticoagulant, 457 patients received warfarin and 397 patients used rivaroxaban. Multivariable analysis showed that, of all the warfarin groups, patients with an international normalized ratio (INR) below 2, good INR control, or poor INR control had a significantly lower risk of mortality compared with that of patients without anticoagulants (HR 0.309, p = 0.0001; HR 0.387, p = 0.0238; HR 0.363, p < 0.0001). Multivariable Cox proportional hazard analyses demonstrated that, compared with the no anticoagulant group, all rivaroxaban dosage groups (≤10 mg, HR 0.456, p = 0.0129; 15 mg, HR 0.246, p = 0.0003; 20 mg, HR 0.264, p = 0.0237) were significantly associated with a lower risk of mortality. Conclusion: Despite effects being smaller than observed with recommended optimal anticoagulation, the use of warfarin with an INR below 2, poor INR control and the use of low-dose rivaroxaban may still provide survival benefits, suggesting viable alternatives that enable physicians to better resolve decisional conflicts concerning the risks and benefits of anticoagulant therapies, as well as for patients in need of but unable to receive standard anticoagulant therapy due to bleeding risk or other factors, such as financial burden, concerns of adverse outcomes, as well as low treatment compliance and persistence.